Trace element assessment in Neoechinorhynchus agilis (Rudolphi, 1918) (Acanthocephala: Neoechinorhynchidae) and its fish hosts, Mugil cephalus (Linnaeus, 1758) and Chelon ramada (Risso, 1827) from Ichkeul Lagoon, Tunisia. (2nd November 2021) - Jmii Chine, H.; Nachev, M.; Sures, B.; Gargouri, L.
Abstract: Acanthocephalans belonging to the species Neoechinorhynchus agilis were collected from two mullets, Mugil cephalus and Chelon ramada from Ichkeul Lagoon in northern Tunisia. Collected parasites, as well as tissues of their hosts (muscle, liver and intestine), were analysed for trace elements (silver, arsenic, cadmium, cobalt, copper, iron, manganese, nickel (Ni), lead (Pb), selenium, vanadium (V), zinc) using inductively coupled plasma mass spectrometry. Our results showed different accumulation patterns of trace elements in fish tissues and parasites. Among the host tissues, liver accumulated the highest metal amounts. Acanthocephalans showed Ni, Pb and V in significantly higher concentrations compared to their host's tissues. Further, the calculated bioconcentration factors demonstrated a 390-fold higher Pb accumulation in the parasite compared to fish muscle. This study is the first field survey in Tunisia dealing with elements' uptake in parasites and their hosts. Our results corroborate the usefulness of the acanthocephalans for biomonitoring of metal pollution in aquatic ecosystems and promote more research in order to understand host–parasite systems in brackish waters of the Mediterranean area.